Explaining the number of social media fans for North American and European professional sports clubs with determinants of their financial value - Nicolas Scelles; Boris Helleu; Christophe Durand; Liliane Bonnal; Stephen Morrow (International Journal of Financial Studies, 2017)
The aim of this article is to investigate the explanatory variables of the number of Facebook fans and Twitter followers for professional sports clubs based on the financial value literature. Such explanatory variables are related to local market conditions and on-field and off-field performance. Based upon a sample of North American major league clubs and the most valuable European soccer clubs as evaluated by Forbes over the 2011-2013 period (423 observations), our results indicate a range of variables with a significant positive impact on the number of social media fans: population, no competing team in the market, current sports performance, historical sports performance, facility age, attendance, operating income, expenses/league mean, and being an English football club. An improved understanding of the effectiveness of clubs' social media presence is important for contemporary sport managers in terms of enhancing supporter communication, involvement, and accountability, as well as maximizing clubs' revenue generation possibilities. Our findings could help sport managers to realize their clubs' social media potential in pursuit of these objectives, specifically to understand which variables are under-exploited and why some clubs over-perform, which will allow managers to prioritize decisions to increase their number of social media fans and financial value.
Keywords: L83; Z23; 330; social media; Facebook fans; Twitter followers; professional sports clubs; North America; Europe; local market variables; on-field and off-field performance variables; financial value